El ambiente social y la influencia en los trastornos de conducta en niños de Educación Básica Elemental - Prado Navarrete, Stefanie Alexandra (2025)
The thesis addresses the influence of the social environment on the onset and development of behavioral disorders in elementary school children. Through a mixed approach, it analyzes how family, school, and community factors impact the prevalence and severity of these disorders. The research includes the application of questionnaires to parents and teachers, and the evaluation of results through descriptive and correlation analysis. The findings show that a favorable social environment, characterized by a stable family setting, emotional support, and participation in community activities, has a positive effect on reducing symptoms of behavioral disorders. Conversely, the absence of these elements can exacerbate issues such as inattention, hyperactivity, and challenging behaviors. Based on these findings, an integrated intervention program is proposed, which includes parenting workshops for parents, teacher training, and the promotion of extracurricular activities for children. The program aims to improve family dynamics, strengthen behavioral management in the classroom, and foster social integration within the community. The thesis concludes that intervention at multiple levels of the social environment is crucial for preventing and treating behavioral disorders in children and recommends the implementation of policies and programs that promote more inclusive and supportive environments for these students.